English Medium Instruction (EMI) in Higher Education: Insights from Indonesian Vocational Lecturers - Simbolon, Nurmala Elmin (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
Reported studies show that some common reasons for offering courses in English medium instruction (EMI) seem to be pragmatic. The rationales for the internationalization of higher education are to improve the English proficiency of both lecturers and students and to facilitate global mobility. However, this responsive practice has some challenges, including limited understanding among university stakeholders of the implications of implementing EMI. This quantitative study examined lecturers' perceptions of EMI in a selected vocational university in Indonesia. A set of four-point Likert scale questionnaires was distributed to 41 lecturers in eight departments, who were selected through simple random sampling to ensure their status as the department's content lecturers. The survey responses were statistically analyzed using SPSS software version 22. The findings showed that the lecturers agreed with all three main issues: terms used as a reference to EMI, EMI practice in the classrooms, and necessary support for EMI implementation, with average means of 2.10, 1.96, and 1.73, respectively (1 = strongly agree, 2 = agree, 3 = disagree, 4 = strongly disagree). These key findings highlight the existence of higher education internationalization and the tension among lecturers in understanding the pedagogical implications of EMI on language use and the assessment of student learning. The main findings also support the need for clear and specific arrangements for EMI implementation in many contexts globally. In response to the increasing trend of EMI in the future education system, we suggest vocational higher education institutions nurture code-switching in EMI classes, adopt content-based English courses, and collaborate between English and EMI content lecturers.